Systems integration '90 : proceedings of the First International Conference on Systems Integration, Morristown, NJ, April 23-26, 1990 - International Conference on Systems Integration (1st : 1990 : Morristown, NJ); Ng, Peter A. (Los Alamitos, CA : IEEE Computer Society Press, 1990)
16